2023
DOI: 10.3389/fpls.2023.1110685
|View full text |Cite
|
Sign up to set email alerts
|

Explore the soil factors driving soil microbial community and structure in Songnen alkaline salt degraded grassland

Abstract: IntroductionSaline-alkali degradation in grassland significantly affects plant community composition and soil physical and chemical properties. However, it remains unclear whether different degradation gradients affect soil microbial community and the main soil driving factors. Therefore, it is important to elucidate the effects of saline-alkali degradation on soil microbial community and the soil factors affecting soil microbial community in order to develop effective solutions to restore the degraded grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…Among them, the bacterial group was significantly positively correlated with soil pH (recall Fig 4A ), and a large number of dominant fungal flora was significantly negatively correlated with soil pH (recall Fig 4B). Our results are consistent with those of previous studies showing that soil pH is the most important driving factor affecting soil bacterial and fungal communities [65,66]. This study found that pH had a significant impact on the soil microbial community, but the dominant microbial flora, such as Acidobacteria, Gemmatimonadetes, Gemmatimonas, Actinobacteria, Kotlabaea, Fusarium, Zygomycota, and Mortierella, had different responses to pH.…”
Section: Influence Of Soil Environmental Factors On the Microbial Com...supporting
confidence: 92%
“…Among them, the bacterial group was significantly positively correlated with soil pH (recall Fig 4A ), and a large number of dominant fungal flora was significantly negatively correlated with soil pH (recall Fig 4B). Our results are consistent with those of previous studies showing that soil pH is the most important driving factor affecting soil bacterial and fungal communities [65,66]. This study found that pH had a significant impact on the soil microbial community, but the dominant microbial flora, such as Acidobacteria, Gemmatimonadetes, Gemmatimonas, Actinobacteria, Kotlabaea, Fusarium, Zygomycota, and Mortierella, had different responses to pH.…”
Section: Influence Of Soil Environmental Factors On the Microbial Com...supporting
confidence: 92%
“…Numerous studies have shown that soil-based physicochemical factors such as soil pH, moisture, and electrical conductivity have important effects on microbial communities ( Wu et al, 2020 ; Chen et al, 2021 ; Bai et al, 2023 ). Soil microbial communities may also be affected by nutrients such as C, N, P, and K ( Moro et al, 2014 ; Huang et al, 2016 ; Batista and Dixon, 2019 ; Ali et al, 2022 ), which regulate soil physicochemical properties and alter the inter-root microecological environment by influencing plant root secretions.…”
Section: Discussionmentioning
confidence: 99%
“…In saline-alkali soil, salt and alkali frequently coexist, presenting a dual stress, and as a response, numerous haloalkaliphiles have emerged, with distinctive structures and physiological adaptations, to thrive in such conditions [2,6]. In the past, both culture-dependent and independent microbial diversity analysis were carried out to understand the microbial community structure [2,7,8], and many novel halophilic and alkaliphilic species were also described from this area [8][9][10][11][12]. During microbial diversity analysis of such an ecosystem, strains HR 1-10 T and J-A-003 T were isolated.…”
Section: Introductionmentioning
confidence: 99%